MEMBANGUN PEMAHAMAN KONSEP DASAR MATEMATIKA PADA ANAK BERKESULITAN BELAJAR MATEMATIKA DI MI - sulthon sulthon (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
This study aims to: 1) find out the types of mathematics learning difficulties experienced by MI students, 2) find out the factors that cause difficulty learning mathematics of MI students, and 3) know the concepts and understanding of mathematics to overcome the difficulties of learning mathematics at Students Islamic Elementary School (MI).The research method used in this study is qualitative. The subjects of this study were two math subject teachers and sixs students who indicated mathematics learning difficulties. While the data collection techniques are observation, interviews, and documentation. Data analysis was carried out with descriptive analysis with data reduction, data presentation, and conclusion drawing.The results showed that: 1)Types of Mathematics learning difficulties experienced by MI / SD students include are, (1) low basic Mathematics skills relating to reading errors understanding the problem; transformation, answer writing process skills; (2) concept errors occur which include: errors in determining the theorem / formula, not writing theorem / formula; (3) procedural error, that is, the inability to manipulate the working steps of Mathematics and not using reasoning conclusions correctly; (4) computational errors that consist of errors in manipulating operations, and do not check the results of the calculation again; 2. Factors causing the difficulty of learning Mathematics MI students are, (1) internal factors, namely low interest and motivation to learn, low intellectual ability, and wrong perceptions of Mathematics, and not mastering the basic concepts of Mathematics; (2) external factors namely the teacher, the teacher lacks mastery of Mathematics material, the teacher does not understand the characteristics of students in learning, the teacher is less able to use active learning techniques, the lack of fulfillment of student books, the school environment is less supportive, and the community environment; 3. efforts to overcome the learning difficulties of MI students' Mathematics are, (1) building basic concepts of Mathematics and understanding proper Mathematics by teaching concepts, principles, with language that is easy for students and linking students' daily experiences; (2) re-teaching Mathematical concepts with theories or formulas that have been learned; (3) the development of students' intuitive thinking; (4) rebuild procedural Mathematics by repeating mathematical problems or problems by paying attention to facts, concepts, and principles that have been learned; (5) provide Mathematical remidial learning guidance. Keywords: learning difficulties, mathematics, islamic elementary school (MI) Abstrak Penelitian ini bertujuan untuk: 1) mengetahui jenis kesulitan belajar Matematika yang dialami siswa MI, 2) mengetahui faktor penyebab kesulitan belajar Matematika siswa MI, dan 3) mengetahui upaya mengatasi kesulitan belajar Matematika siswa MI. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif. Subjek penelitian ini adalah dua guru mata pelajaran matematika dan 6 siswa yang terindikasi kesulitan belajar matematika. Sedangkan teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan analisis deskriptif dengan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1). Jenis kesulitan belajar Matematika yang dialami siswa MI/SD meliputi: (1) rendah keterampilan dasar Matematika yaitu berkaitan dengan kesalahan membaca soal, memahami masalah, transformasi, keterampilan proses penulisan jawaban; (2) terjadi kesalahan konsep yang meliputi: kesalahan dalam menentukan teorema/rumus, tidak menuliskan teorema/rumus; (3) kesalahan prosedural yaitu, ketidakmampuan memanipulasi langkah-langkah pengerjaan Matematika, dan tidak menggunakan penalaran kesimpulan dengan benar; (4) kesalahan komputasi yang terdiri dari kesalahan dalam memanipulasi operasi, dan tidak memeriksa hasil hitungannya kembali; 2). Faktor penyebab kesulitan belajar Matematika siswa MI adalah, (1) faktor internal yaitu minat dan motivasi belajar rendah, kemampuan intelektual rendah, persepsi yang salah terhadap Matematika, dan tidak dikuasainya konsep-konsep dasar Matematika; (2) faktor eksternal yaitu guru, guru kurang menguasai materi Matematika, guru tidak memahami karakteristik siswa dalam belajar, guru kurang mampu menggunakan teknik pembelajaran aktif, kurang terpenuhinya buku siswa, lingkungan sekolah kurang mendukung, dan lingkungan masyarakat; 3) upaya untuk mengatasi kesulitan belajar Matematika siswa MI adalah, (1) membangun konsep dasar Matematika serta pemahaman Matematika yang tepat dengan mengajarkan konsep, prinsip, dengan bahasa yang mudah bagi siswa serta mengaitkan pengalaman sehari-hari siswa; (2) mengajar kembali konsep Matematika dengan teori-teori atau rumus-rumus yang telah dipelajari; (3) pengembangan berpikir intuitif siswa; (4) membangun kembali procedural Matematika dengan mengulang kembali soal-soal atau permasalahan matematika dengan memperhatikan fakta-fakta, konsep-konsep, dan prisip yang pernah dipelajari; (5) memberikan bimbingan pembelajaran remidial Matematika. Kata Kunci: Kesulitan belajar, matematika, Madrasah Ibtidaiyah.